(untitled) (Sudurpaschim Spectrum, 2024)
Geta Eye Hospital (GEH) established in 1981 under the Government of Nepal’s Prevention and Control of Blindness Project, GEH has played a transformative role in healthcare, diplomacy, and development. With financial support from the Norwegian Agency for Development Cooperation (NORAD) and Norwegian Church Aid (NCA), and technical guidance from the World Health Organization (WHO), GEH has provided critical ophthalmic services for over four decades. The hospital has treated more than 1.92 million Indian patients, including 407,657 individuals who underwent eye surgeries, primarily cataract operations. This immense contribution to eye health has positioned GEH as a key institution fostering Nepal-India bilateral relations. This study explores the hospital’s impact on medical tourism, cultural exchange, and economic ties, analyzing its role in strengthening cross-border cooperation. Using descriptive and analytical methods, and drawing on both primary and secondary sources, the research frames GEH’s influence through the lens of Liberal International Relations theory, emphasizing cooperation and interdependence. The study highlights that GEH has built trust among India’s low- and middle-income populations, fostering a "Netra-Prakash" (eye-sight) bond that transcends borders. By facilitating medical tourism and public diplomacy, the hospital has contributed to people-to-people relations, modest foreign currency earnings, and cultural exchange in the border regions. Additionally, GEH has enhanced the capacities of local organizations and fostered cross-border collaborations, exemplifying the effective use of soft power in international relations. Despite its limited international scope, GEH has made a commendable contribution to Nepal-India bilateral relations, serving as a model for healthcare diplomacy. This paper underscores the need for further research and policy attention to maximize the hospital’s potential in promoting sustainable development and regional cooperation.